The model of harmful ejections dissemination of the transport flows made on the basis of the calculation of the turbulent diffusion equation - Komarov, Jury; Fedotov, Vitali (Transport, 2006)
Toxic gases and fine dispersive particles are pumped out into the atmosphere from a transport flow. The particles sizing less than 10,0 micro metres (PM10–2,5) remain in the suspension for a long time due to the thermal stream and the Brownian motion; as for the surface of the layer which is between the gas molecules and solid particles ‐ it doesn't exist. This fact allows us to study the mixture of the toxic gases and solid particles as if it is a mixture of physically homogeneous particles, and the model of their spreading can be pretended as a dissemination of a phase component in the thermodynamic system according to the diffusion laws. In this paper we refer to the calculation of the parameters of the model of the toxic ejections dissemination in the ecologically unsafe part of the main transport line. The calculation was based on the equation of the turbulent diffusion. The results of the research are intended to control the movement of the traffic on the urban mains according to ecological requirements, creating the industrial technology of refining atmospheric air of urban mains.First Published Online: 27 Oct 2010